2022
DOI: 10.3389/fphys.2022.868902
|View full text |Cite
|
Sign up to set email alerts
|

The Performance-Result Gap in Mixed-Reality Cycling – Evidence From the Virtual Tour de France 2020 on Zwift

Abstract: Background: Mixed-reality sports are increasingly reaching the highest level of sport, exemplified by the first Virtual Tour de France, held in 2020. In road races, power output data are only sporadically available, which is why the effect of power output on race results is largely unknown. However, in mixed-reality competitions, measuring and comparing the power output data of all participants is a fundamental prerequisite for evaluating the athlete’s performance.Objective: This study investigates the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
(55 reference statements)
1
5
0
Order By: Relevance
“…Zwift (Zwift Inc., Long Beach, CA, USA), a bicycle simulation software, and a roller fixture (Tacx NEO T2 Smart Trainer, Garmin Korea Ltd., Seoul, Republic of Korea) were used to eliminate external factors that might affect the research results, such as weather, wind, traffic, and road conditions, and to provide the same cycling environment [ 28 , 29 ]. The cumulative altitude per 10 km cycling was 62 m, the longest uphill section was 1.5 km, and the cumulative altitude was 18 m. The participants cycled 10 km each during the first and second cycling sessions.…”
Section: Methodsmentioning
confidence: 99%
“…Zwift (Zwift Inc., Long Beach, CA, USA), a bicycle simulation software, and a roller fixture (Tacx NEO T2 Smart Trainer, Garmin Korea Ltd., Seoul, Republic of Korea) were used to eliminate external factors that might affect the research results, such as weather, wind, traffic, and road conditions, and to provide the same cycling environment [ 28 , 29 ]. The cumulative altitude per 10 km cycling was 62 m, the longest uphill section was 1.5 km, and the cumulative altitude was 18 m. The participants cycled 10 km each during the first and second cycling sessions.…”
Section: Methodsmentioning
confidence: 99%
“…With the advent of virtual training programs like Zwift TM , 9,11 athletes can now run and bike in virtual environments at home while on the stationary bike trainer or treadmill. Coaches had varying views as to whether Zwift is a serious training tool.…”
Section: Technology For Performancementioning
confidence: 99%
“…The use of technologies in triathlon includes the use of wearables such as global positioning system (GPS) sports watches for measuring distance and intensity, 6 inertial measurement units (IMUs) for measuring running-related metrics, including run power 7 and heart rate measurement straps that use electrocardiograph (ECG) like electrodes to capture heart rate data. 8 Non-wearable digital hardware includes equipment, such as cycling smart trainers, 9 bike power meters, 10 software platforms that support virtual training, 11 and the monitoring and analysis of training and competition data. 12 Some aspects of performance cannot easily be measured, for example, flow and how in-tune the athlete is with what is going on inside their body.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that sports competitions should be cancelled, postponed or rearranged respcted to COVID19 protocols and without spectators [12]. In addition, several data recorded that several international sport events had to be postponed, such as the Olympic Games in Japan [13,14] and the European Football Championship for men, a football league in Sweden [15], UEFA Euro 2020, Tour de France [16], tennis tournaments, cycling classic ParisRoubaix 2020 [17]. The policies to stop or postpone the competition caused financial losses, for example the League Premier had to lose $1.25 billion in revenue, Tokyo 2020 Olympics had to lose more than $13 billion [18].…”
Section: Introductionmentioning
confidence: 99%